Penerapan Pendekatan Multimodal dalam Pembelajaran Abad 21 di Sekolah Dasar: Sebuah Tinjauan Pustaka - Syifa Hasna Fauziyah; Yeni Yuniarti (Universitas Muhammadiyah Kuningan, 2024)
The paradigm shift in education due to the development of the times requires learning activities to adapt to the times. Multimodal approach is an approach that prepares learning in 21st century classrooms. Multimodal approach in learning involves various modes to achieve the meaning of learning activities. This multimodal approach is important to use in learning. This research aims to find out how the application of multimodal approach in 21st century learning especially in elementary school. This research uses a qualitative method with the type of literature study (library research). The data used in this research is by reviewing books, journal literature, thesis and dissertation research results, and the internet. The results showed that 21st century learning emphasises learning that is oriented towards interactive, holistic, dynamic, collaborative and student-centred learning. Based on this, the multimodal approach can be used as an alternative in the learning process in schools with diverse backgrounds.